Calculation of Involved and Noninvolved Organs Doses in Carbon Therapy of Brain Tumor Using GEANT4 Simulation Toolkit - Maria Ahmadi; Seyed Mohammad Motevalli; Payvand Taherparvar; Vahid zanganeh (Iranian Journal of Medical Physics)
Introduction: This study used the GEANT4 Monte Carlo toolkit for radiation transport simulations in brain carbon therapy, incorporating a human phantom model to accurately assess dose delivery to targeted and non-targeted organs. Weight factors were employed to generate a Spread Out Bragg Peak (SOBP).Material and Methods: The study used the ORNL-MIRD phantom to simulate carbon therapy for brain tumors, finding that the optimal energy range for carbon ions was 2420-2560 MeV to effectively cover the tumor. To achieve a homogeneous radiation dose, a Spread Out ragg Peak (SOBP) was generated using multiple Bragg peaks with specific intensity factors. Beam parameters were also evaluated per ICRU guidelines.Results: This study estimated the flux and dose distributions of secondary particles—protons, electrons, neutrons, alpha particles, and photons—in the brain tumor and surrounding tissues. We calculated the cumulative dose from both carbon ions and secondary particles, finding an absorbed dose ratio of 0.003 in healthy brain tissue compared to the tumor, with values of 4.8 × 10-4 for the skull and 2.6 × 10-5 for the thyroid. Notably, neutrons and photons can significantly increase energy transfer to distant organs, raising secondary cancer risk.Conclusion: The findings presented in this article demonstrated that the involvement of secondary particles in the dose received by both the brain and other organs remains minimal, as the highest absorbed dose was predominantly localized within the tumor.